Gene expression and proteomic analysis underlying adipogenesis in livestock - Campos, Carolina Filardi de (2016)
Marbling or intramuscular fat (IMF) is an important component of livestock production, as it is a major factor in the overall meat quality. IMF is achieved by adipogenesis, the process of proliferation and differentiation of preadipocytes, and lipogenesis, with the subsequent assimilation of lipid. The understanding of events that occur during preadipocyte differentiation has advanced considerably in the last few years and has relied mainly on the use of tissue culture models of adipogenesis. Animal models can be used not only for a better understanding of fat deposition in livestock, but also as models to an increased comprehension on molecular mechanisms behind human conditions. Furthermore, adipocyte differentiation has many implications for human disease conditions. It is well known that this differentiation involves a transcriptional cascade, so the present study provided knowledge about genes and transcription factors using RT-qPCR technique, involved in differentiation of preadipocytes into mature adipocytes comparing two divergent pig breeds. The results show us that some genes are differentially expressed between commercial line and Piau breed. Moreover a gene expression and a proteomic study are provided revealing the effects of vitamin A on adipogenesis in cattle, revealing the negative effect on adipogenesis. Thereby, we highlighted the importance of gene expression and proteomic studies to increase the understanding of molecular mechanisms underlying adipogenesis.